The biology and population ecology of the Namaqua dune mole-rat, Bathyergus janetta from the Northern Cape Province, South Africa - Bennett, Nigel Charles (University of Pretoria, 2024)
Dissertation (MSc (Zoology))--University of Pretoria, 2002.